2018
DOI: 10.1159/000484228
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire-Based Survey on Gastrointestinal Bleeding and Management of Antithrombotic Agents during Endoscopy Among Asian Countries

Abstract: Objective: Guidelines on the management of antithrombotic therapy for endoscopic procedures vary among countries. Differences in the management of antithrombotic agents for endoscopic procedures between Western and Eastern countries have already been reported. However, no study has investigated the differences among Asian countries. The aim of this study was to examine the differences in the etiology of gastrointestinal bleeding and management of antithrombotic agents during endoscopic procedures between Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The incidence of upper GI bleeding was affected by several factors, including peptic ulcers, gastroesophageal varices, GERD, Mallory-Weiss tears, and prescription of antithrombotic agents and NSAIDs, as previously demonstrated. (1,7,(10)(11)(12)(13)(17)(18)(19) The decrease in the incidence of upper GI bleeding synchronized with the diminished incidence of peptic ulcers from 2009 to 2014, as indicated in Fig. 1B.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The incidence of upper GI bleeding was affected by several factors, including peptic ulcers, gastroesophageal varices, GERD, Mallory-Weiss tears, and prescription of antithrombotic agents and NSAIDs, as previously demonstrated. (1,7,(10)(11)(12)(13)(17)(18)(19) The decrease in the incidence of upper GI bleeding synchronized with the diminished incidence of peptic ulcers from 2009 to 2014, as indicated in Fig. 1B.…”
Section: Discussionmentioning
confidence: 79%
“…Introduction U pper gastrointestinal (GI) bleeding is a serious and lethal condition especially in older patients, and endoscopic hemostasis and/or radiological intervention are widely applicable therapeutic approaches. (1)(2)(3)(4)(5)(6)(7)(8) Upper GI bleeding can be induced by lesions of the esophagus, stomach, and duodenum, including gastroduodenal ulcers induced by Helicobacter pylori (H. pylori) infection, nonsteroidal anti-inflammatory drugs (NSAIDs), and antithrombotic agents; Mallory-Weiss tears; and gastroesophageal varices. (1,2,(9)(10)(11)(12) The Japan Medical Data Center (JMDC) claims database is a real-world database in Japan that has been available for research purposes since 2005.…”
mentioning
confidence: 99%
“…Several factors might be related to an increased or decreased risk of Barrett's esophagus and colorectal neoplasms, including the bile acid level, 37-39 gastrin level, 29,40,41 genetic factors, [42][43][44] and treatment with nonsteroidal anti-inflammatory drugs and/or aspirin. 29,[45][46][47][48] The present chart review did not evaluate these factors. There were also several other limitations in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Several factors might be related to an increased or decreased risk of Barrett's esophagus and colorectal neoplasms, including the bile acid level, gastrin level, genetic factors, and treatment with nonsteroidal anti‐inflammatory drugs and/or aspirin …”
Section: Discussionmentioning
confidence: 99%
“…6 Another survey from Japan reported that endoscopists were more likely to discontinue anticoagulants compared with antiplatelets. 7 In this survey, the respondents were given a certain situation and were asked if they would perform the endoscopic procedure if the patient was taking antithrombotics. For example, the respondents were asked if they would perform a biopsy in patients with an active gastric ulcer if the patient was taking aspirin.…”
mentioning
confidence: 99%